THE ANALYSIS OF FACTORS INFLUENCING DIVIDEND PAYOUT RATIO IN INSURANCE COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (IDX) PERIOD 2011-2015. - Liono, Marcelita .; Lambey, Linda .; Tumiwa, Johan . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: This study aims to analyze factors which are Profitability, Growth Opportunity, Firm Size and Leverage that influence the Dividend Payout Ratio in insurance companies listed in Indonesia Stock Exchange period 2011-2015. This study is a quantitative study and Multiple Linear Regression used as analysis tool. The sample are 10 companies who already made IPO before year 2011 and data were gathered from the company annual financial report. Result shows that Profitability measured by ROE and Growth Opportunity have a significant and negative association with DPR. Meanwhile Firm Size and Leverage have insignificant and negative relation with the DPR in insurance companies that listed in IDX. The negative association by ROE and Growth Opportunity to the DPR. It thus, tends to retain their earnings more than to pay it as dividend. Companies should improve their product so they can cover all of the customer needs.Â Keywords: dividend payout ratio, insurance company, profitability, growth opportunity, firm size, leverage